2007
DOI: 10.1007/s11199-007-9222-4
|View full text |Cite
|
Sign up to set email alerts
|

‘How Can I Feel for Others When I Myself Am Beaten?’ The Impact of the Armed Conflict on Women in Israel

Abstract: This research presents an initial documentation of Israeli women's sense of insecurity during the Second Intifada (2001)(2002)(2003)(2004)(2005). Drawing on feminist security theory and the intersectional approach to gender, we hypothesized that women's familiar tendency to develop high levels of stress following political violence would be related to previous sexual and domestic victimization, to economic distress and ethnic discrimination among minority women, and to the cultural role of care workers among w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Admittedly, our choice to listen to Israelis living near Gaza is a continuation of previous efforts to understand the complex impact of the ongoing conflict in Israel/ Palestine on women (see also : Sachs et al, 2007). We assume that documenting the communal caring practices carried out by Jewish-Israeli women living near Gaza, as well as their victimhood narratives, serves two purposes.…”
Section: The Political Economy Of Care In Conflictmentioning
confidence: 99%
“…Admittedly, our choice to listen to Israelis living near Gaza is a continuation of previous efforts to understand the complex impact of the ongoing conflict in Israel/ Palestine on women (see also : Sachs et al, 2007). We assume that documenting the communal caring practices carried out by Jewish-Israeli women living near Gaza, as well as their victimhood narratives, serves two purposes.…”
Section: The Political Economy Of Care In Conflictmentioning
confidence: 99%
“…At the same time, women are often overrepresented in occupations involving intensive interpersonal interactions and caretaking responsibilities (e.g., nursing and teaching), where they are expected to be strong for others (e.g., patients and children; e.g., Sachs, Sa'ar, & Aharoni, 2007). The burden of caring for others may expose women to a constant struggle to try to maintain control while feeling tremendously vulnerable, a struggle to display certain emotions (e.g., cheerfulness) while hiding genuine emotions (e.g., fear; Hochschild, 1983).…”
Section: The Moderating Effect Of Gendermentioning
confidence: 99%
“…Although not claiming an ecological orientation, some studies considered the mediating roles of various contextual factors (e.g., Haj-Yahia 2008;Kerestes 2006;Punamaki 1990;Qouta et al 2008;Sachs et al 2007) in models that seek to explain the effects of political violence on individuals.…”
Section: Research Findingsmentioning
confidence: 99%
“…Minority status and socioeconomic class, factors widely accounted for in the social sciences, have been found to mediate experiences of political violence (e.g., Sachs et al 2007;Cummings et al 2009). Sachs et al reported that "poverty, minority status and gender/sexual injuries exacerbate trauma that results from assaults perpetrated on national backgrounds."…”
Section: Research Findingsmentioning
confidence: 99%